A Comparative Study of Lidocaine and Lidocaine Mannitol in Anesthetizing Human Teeth with Inflamed Pulps - Talati, Ali; Bidar, Maryam; Sadeghi, Ghazal; Nezami, Hossein (Iranian Endodontic Journal, 2010)
INTRODUCTION: Failure to achieve adequate and profound anesthesia in teeth with acute pulp inflammation is a common condition during emergency visits in root canal therapy. Many different anesthetic solutions such as morphine and capsaicin have accordingly been examined. Mannitol an alcoholic sugar with high osmotic pressure level- is applicated for reducing intracranial and post retinal pressure in medicine. It has also been used for its diuretic effect. In combination with local anesthetic solution, it increases permeability of the nerve fiber sheath and leads to influx of the local anesthetic through cytoplasmic membrane .The purpose of the present study was to compare the efficacy of routine local anesthesia with or without using mannitol in teeth with inflamed pulps. MATERIALS AND METHODS: one hundred patients with acute dental pain in posterior teeth were selected. Vials with 3 ml anesthetic solution containing 2.5% lidocaine with 1/80000 epinephrine or 2.5% lidocaine with 1/80000 epinephrine and 0.5 mol mannitol were used for anesthesia. For each patient, the routine injection technique was applied, during the removal of decay and dentine. Depth of anesthesia was evaluated and the supplementary injection was done in case of pain feeling and then pulpotomy was done. The analysis of data was done using chi-square statistical test. RESULTS: The results showed that complete anesthesia after the first injection was obtained with lidocaine mannitol in 46% and with lidocaine alone in 38% of cases. However, the difference was not significant. CONCLUSION: These finding suggest that the addition of mannitol to the standard anesthetic solution could insignificantly increase the level of anesthesia in teeth with inflamed pulps.